Affective and motivational influences in person perception - Kuzmanovic, Bojana; Jefferson, Anneli; Bente, Gary; Vogeley, Kai (Frontiers in Human Neuroscience, 2013)
Interpersonal impression formation is highly consequential for social interactions in private and public domains. These perceptions of others rely on different sources of information and processing mechanisms, all of which have been investigated in independent research fields. In social psychology, inferences about states and traits of others as well as activations of semantic categories and corresponding stereotypes have attracted great interest. On the other hand, research on emotion and reward demonstrated affective and motivational influences of social cues on the observer, which in turn modulate attention, categorization, evaluation and decision processes. While inferential and categorical social processes have been shown to recruit a network of cortical brain regions associated with mentalizing and evaluation, the affective influence of social cues has been linked to subcortical areas that play a central role in detection of salient sensory input and reward processing. In order to extend existing integrative approaches to person perception, both the inferential-categorical processing of information about others, and affective and motivational influences of this information on the beholder should be taken into account.